Ecological Validity and the Evaluation of Avatar Facial Animation Noise - Wilczkowiak (SHE/HER), Marta; Jakubzak, Ken; Clemoes, James; Treptow, Cornelia; Read, Kerry; Porubanova, Michaela; McDuff, Daniel; Kuznetsova, Marina; Rintel, Sean; Gonzalez-Franco, Mar (Workshop Series on Animation in Virtual and Augmented Environments (ANIVAE 2024), 2024)
Facial animation noise levels affect the acceptance of avatars in communication systems. However, there is no standard for evaluation, especially with regard to ecological validity. We investigate low and high ecological validity on two within-subjects experiments conducted in Augmented Reality on a Hololens2. We simulated facial-expression noise introduced on stylized cartoon avatars, and found that in the high ecological validity experiment, subjects were less sensitive to noise parameters, but their judgement was more influenced by empathy scores and gender biases. This highlights the importance of considering both technical parameters and user experience when designing communication systems. We make some general recommendations for evaluating issues of avatar acceptance given the trade-offs between the approaches, and propose the ‘Triple C’ factors of Context, Culture and Character as an important set of ecological factors to consider. MSR Blog on this research: Exploring how context, culture, and character matter in avatar research